Pengaruh Pemberdayaan Dan Lingkungan Kerja Terhadap Produktivitas Rumah Tangga Sasaran Pada BUMDesa Sejahtera Desa Dringu Kabupaten Probolinggo - Dimas Aditya Eka Wardana; Abdul Kodir Djaelani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis study aims to describe and analyze the effect of empowerment and work environment on the productivity of targeted households in BUMDesa Sejahtera Customs Village simultaneously or partially by statistical tests. The sample consisted of 59 target household members from a population of 142 target household members. Data collection through the distribution of questionnaires and supporting data. In analyzing the data, this study was assisted by SPSS version 25. The analytical tools used in this study included the instrument test, normality test, classical assumptions, multiple linear regression analysis, and hypothesis testing. The analysis showed that partially empowerment had a negative effect on the productivity of the target households, while the work environment had a positive effect on the productivity of the target households of BUMDesa Sejahtera Desa Pabean. A simultaneous ceremony showed that empowerment and the work environment had a positive effect on the productivity of target households in BUMDesa Sejahtera, Customs Village.Keywords: Empowerment, Work Environment, Productivity